Analisis Dampak dan Strategi Toko Kelontong dalam Menghadapi Maraknya Toko Online: Studi Kasus Salah Satu Toko Gejlig, Kecamatan Kajen, Kabupaten Pekalongan - Azizah, Lutfiyah; Reswari, Meike Ardhana; Khafidz Ma’shum, Muh. (CV. Lafadz Jaya, 2024)
As time goes by, technology is getting more advanced. Many stores provide delivery services or market places. One of them is a grocery store. A grocery store is a store that provides daily necessities. My purpose of researching is to find out whether technological developments have an impact on grocery store income. The research method we use is a descriptive qualitative research method with a case study approach and using primary data sources by conducting interviews and observations. The results of the study showed that technological developments did not affect grocery store income because grocery stores provide daily necessities so that they are very much needed in basic needs. The strategy used in maintaining a grocery store is to take an emotional approach. By being ethical, friendly, disciplined, honest, treating customers like kings, and especially allowing delays in payment. So that customers will be satisfied with our service. By maintaining good relationships with customers, the supply of goods in the store will be smooth, prices are more friendly, helping sellers when there are obstacles with suppliers, increasing reputation and trust.